Exercise for reducing chemotherapy-induced peripheral neuropathy: a systematic review and meta-analysis of randomized controlled trials - Huang, Yingjie; Tan, Tian; Liu, Lu; Yan, Zijian; Deng, Yuexia; Li, Guangyao; Li, Min; Xiong, Jia (Frontiers in Neurology, 2024)
Background More than half of cancer patients develop severe chemotherapy-induced peripheral neuropathy (CIPN), resulting in low quality of life, negative effects on function, and challenges in treatment compliance. Most recent studies have shown that exercise therapy has a positive impact on reducing CIPN symptoms and can also improve quality of life, balance, and activity levels. The aim of this meta-analysis was to evaluate the effect of exercise therapy on the efficacy of CIPN. Methods Computerized search of Embase, Web of Science, CNKI, Wan Fang Data, VIP, CBM for RCTs on exercise therapy for CIPN from database creation to November 2022, without language restriction. The Cochrane Handbook 5.3 risk of bias assessment tool was used to evaluate the quality of the included studies. Then Revman 5.3 software was used to evaluate the quality of the included studies. The heterogeneity of the research results is tested by I2, continuous variables were presented as weighted mean difference or standard mean difference, and confidence intervals were set at 95%. Stata15.0 was utilized to conduct a meta-analysis. Results A total of 15 RCTs with 1124 patients were included. Meta-analysis showed that the test group was superior to the control group in terms of total symptom score (SMD: -0.62; 95% Cl: -0.99, -0.24), numbness, tingling, quality of life score (total score, physical, function), pain, balance, and neurotoxicity function assessment (FACT/GOG-NTX) questionnaire (P < 0.05). Limitations The duration and frequency of treatment are different every week, which may have some impact on the results. Conclusion Exercise therapy can be effective in treating CIPN by improving symptom score (total symptom score, numbness, tingling), quality of life score (total score, physical function), pain, balance, and FACT/GOG-NTX questionnaires. It still needs to be refined and validated by more high-quality, multicenter, large-sample RCTs in the future. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022373131, identifier: CRD42022373131.